Reduction rate of nematode egg counts and third-stage larvae development from sheep and goat faeces preserved at 4οC - DRIMTZIA, A.; PAPADOPOULOS, E. (Journal of the Hellenic Veterinary Medical Society, 2018)
Gastrointestinal nematode parasites cause major production losses to small ruminants. The most common way to diagnose or monitor the worm burdens in sheep and goats remains the quantitative parasitological examinations, i.e. the faecal egg counts. However, the reliability of the results of such methods depends greatly on the conditions and duration of the storage of the faecal samples prior to examination. The aim of this research was to evaluate the reduction rate and the maximum storage period, without significant losses, of nematode egg counts and third-stage larvae development from sheep and goat faeces preserved at 4οC. Towards this end, a pooled faecal sample was formed by collecting faeces from naturally infected sheep and goats (separately). Faecal egg counts and coprocultures were performed on fresh faeces and on preserved ones every week and up to 119 days post sampling. It was concluded that the preservation at 4oC, i.e. into a refrigerator, of fresh faeces from sheep and goats for parasitological examinations poses danger of misdiagnosis, if not performed in a period not exceeding 3 weeks of time. The rate of reduction of the faecal nematode egg counts starts to be significant lower than the ones performed with fresh samples, for both sheep and goats, after the third week of storage. The percentage of the gastrointestinal nematode larvae developing to the infective third–stage alters significantly for the Haemonchus genus, soon after the first week of storage (p<0.05).